Qualitative research for international business - Doz, Yves (Journal of International Business Studies, 2011)
Qualitative research in international business has been rare, the main research streams of the field relying more on quantitative methods. This paper first outlines why qualitative research has been scant. It then presents areas, such as theory building, where qualitative research could make a substantial contribution. Third, it reviews approaches to high standards of qualitative research and criteria for evaluating qualitative research. Finally, some possible research areas where qualitative research might prove fruitful are suggested.